Transient Left Ventricular Apical Ballooning (Takotsubo Cardiomyopathy): Mimicking Acute Coronary Syndrome - Ahsan, Mohammad Razib; Rahman, Md Mukhlesur; Bhuiyan, AKM Mohiuddin; Ahmed, Md Khurshed; Siddique, Md Abu; Sultan, Md Ashraf Uddin (University Heart Journal, 2012)
No abstract available DOI: http://dx.doi.org/10.3329/uhj.v7i2.10848 University Heart. Journal Vol. 7, No. 2, July 2011